Selected Physical Geographical characteristics of Radlje ob Dravi Municipality - Žiberna, Igor (Journal for Geography, 2011)
The article treats relations between land use and selected physical geographical charactersitics of Radlje ob Dravi municipality. Methodology of gathering data and statistical analysis is presented. Within geographical information system methodology the frequency of land use categories and their connection with physical geographical characteristics are analysed.